The Cascading Effects of CEO Dark Triad Personality on Subordinate Behavior and Firm Performance: A Multilevel Theoretical Model. Issue 2 (April 2020) - Palmer, Joshua C.; Holmes, R. Michael; Perrewé, Pamela L.
Chief executive officer (CEO) personality has emerged as a key predictor of firm performance. A burgeoning literature rooted in psychology has shown that leaders with the dark triad personality traits (i.e., narcissism, Machiavellianism, and psychopathy) can have harmful effects on organizations. However, scholars have not fully illuminated the "black box" of processes that explain how and why CEO dark personality matters. Specifically, we know little about the microfoundations of CEOs' influence: how and why do the effects of CEO dark personality cascade down to affect employees and outcomes throughout the different levels of the firm. Therefore, we explore how CEOs' personalities shape their relationships with other top management team (TMT) members and how these relationships affect other employees in the organization. Specifically, drawing on upper echelons theory and social exchange theory, we provide a multilevel theoretical model examining how distinct CEO dark triad traits shape CEO–TMT exchange quality, TMT destructive leadership, TMT behavioral integration, subordinates' counterproductive work behaviors, and ultimately firm performance. Implications for theory, future research, and practice also are discussed.